Dirac Cone Spin Polarization of Graphene by Magnetic Insulator Proximity Effect Probed with Outermost Surface Spin Spectroscopy. (4th April 2018) - Sakai, Seiji; Erohin, Sergei V.; Popov, Zakhar I.; Haku, Satoshi; Watanabe, Takahiro; Yamada, Yoichi; Entani, Shiro; Li, Songtian; Avramov, Pavel V.; Naramoto, Hiroshi; Ando, Kazuya; Sorokin, Pavel B.; et al.
Abstract: The effects of the proximity contact with magnetic insulator on the spin‐dependent electronic structure of graphene are explored for the heterostructure of single‐layer graphene (SLG) and yttrium iron garnet Y3 Fe5 O12 (YIG) by means of outermost surface spin spectroscopy using a spin‐polarized metastable He atom beam. In the SLG/YIG heterostructure, the Dirac cone electrons of graphene are found to be negatively spin polarized in parallel to the minority spins of YIG with a large polarization degree, without giving rise to significant changes in the π band structure. Theoretical calculations reveal the electrostatic interfacial interactions providing a strong physical adhesion and the indirect exchange interaction causing the spin polarization of SLG at the interface with YIG. The Hall device of the SLG/YIG heterostructure exhibits a nonlinear Hall resistance attributable to the anomalous Hall effect, implying the extrinsic spin–orbit interactions as another manifestation of the proximity effect. Abstract : Outermost surface spin spectroscopy using spin‐polarized helium reveals a large negative spin polarization of Dirac cone electrons in graphene/yttrium iron garnet (YIG) heterostructure . Despite proximity‐induced spin polarization, key electronic features of graphene are found to be preserved in graphene/YIG heterostructure reflecting nonchemical nature of interfacial interactions. Extrinsic spin–orbit interactions in graphene also suggested from nonlinear Hall resistance.